Enhanced Sensitivity and Precision of Portable Mass Spectrometry (MS) with a Discontinuous Atmospheric Pressure Interface by Multiple Ion Injection. (22nd January 2022) - Li, Jun; Wu, Huanming; Yu, Jiancheng; Zhang, Junliang; Wang, Chenlu; Xu, Fuxing; Wang, Weimin; Xie, Zhibin; Yin, Tao; Tang, Keqi
Abstract: The detection limit is one of the most important performance characteristics for portable mass spectrometers (MS). To significantly reduce the size and the weight, small vacuum pumps are used in portable MS which leads to the use of a discontinuous atmospheric pressure interface (DAPI). Multiple ion injections (M-DAPI), which accumulates ions through opening the DAPI pinch valve several times during the ion injection period while maintaining a radio frequency (RF) voltage continuously on the trap, was shown to improve the sensitivity of DAPI-based portable MS. A systematic investigation of the optimization of M-DAPI was performed. The primary parameters affecting the performance of M-DAPI were optimized and sensitivity and stability improvements are reported. An 11.6-fold improvement in sensitivity was achieved by M-DAPI compared to the single ion injection DAPI operation for 1 μg/mL enrofloxacin. A more than 10-fold reduction in the limit of detection (LOD) to 0.01 μg/mL was also obtained. In addition, the stability was improved by M-DAPI with a relative standard deviation of 14.4% compared to 4.6% for DAPI.